2009
DOI: 10.1002/cii.376
|View full text |Cite
|
Sign up to set email alerts
|

The importance of intra-operative imaging during cochlear implant surgery

Abstract: Two unusual cases of cochlear implant (CI) surgery complication are reported: introduction of the electrode array into the superior semicircular canal with normal morphology and a growing amplitude of neural potential (neural response imaging, NRI) during intra‐operative monitoring control. In the first case, a two‐year‐old patient affected by congenital sensorineural profound deafness was bilaterally implanted with two Clarion 90 k devices and intra‐operative electrophysiological and radiological controls wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The findings of our study argue for routine radiographic position checks because intraoperative findings only have a limited predictive value. This conclusion is in accordance to surgeons who rank radiographic position checks as so important that they perform intraoperative position checks, for example, (9,10), which have the added advantage that instant corrections of electrode position can be performed.…”
Section: Discussionsupporting
confidence: 86%
“…The findings of our study argue for routine radiographic position checks because intraoperative findings only have a limited predictive value. This conclusion is in accordance to surgeons who rank radiographic position checks as so important that they perform intraoperative position checks, for example, (9,10), which have the added advantage that instant corrections of electrode position can be performed.…”
Section: Discussionsupporting
confidence: 86%
“…In another two cases presented by Viccaro et al,17 where the electrode array was misplaced into the superior semicircular canal, stimulated channels gave a response with normal morphology and a growing amplitude at increasing stimulation intensity. It was hypothesized that the near‐normal neural responses obtained were probably due to a spread of the current secondary to the high stimulation intensity, similar to the response observed when the electrode array is placed in the cochlea.…”
Section: Discussionmentioning
confidence: 89%
“…In all cases there was either absent or abnormal intraoperative neural response telemetry that lead to intraoperative imaging. In all revision cases, the cochleostomy was widened antero‐inferiorly to allow correct insertion of the electrode array 13, 17, 18…”
Section: Discussionmentioning
confidence: 99%
“…Both studies cited the risk of cataracts due to radiation exposure and discussed the potential for the preoperative CT scan and possible multiple intraoperative radiographs culminating in a harmful amount of radiation, especially in the pediatric population. However, the other five studies examining intraoperative X‐ray in this systematic review concluded that intraoperative X‐ray was useful . The rate of electrode misplacement across these studies, 2.2%, is low but not negligible, which is considered to be a major complication because accurate placement is critical for successful auditory rehabilitation .…”
Section: Discussionmentioning
confidence: 88%
“…However, the other five studies examining intraoperative X-ray in this systematic review concluded that intraoperative X-ray was useful. 9,12,[22][23][24] The rate of electrode misplacement across these studies, 2.2%, is low but not negligible, which is considered to be a major complication because accurate placement is critical for successful auditory rehabilitation. 19 Revision surgery in these patients incurs additional cost and may cause increased morbidity.…”
Section: Discussionmentioning
confidence: 92%